Local Contractors' Awareness on Competitiveness towards Liberalisation and Globalisation in the Malaysian Construction Industry - Rani, Nur Izzati Ab.; Ismail, Syuhaida; Mohamed, Zainai; Hussain, Affuddin Husairi; Ghafourian, Kambiz (Penerbit Universiti Sains Malaysia, 2018)
Globalisation gives the opportunity to contractors from a particular country to venture into various countries around the globe as the construction market is unlimitedly open. Due to this globalisation, the government has signed free trade agreements (FTA) as the result of the liberalisation process. Globalisation and liberalisation do not only provide opportunities and benefts to the local construction market, but also give challenges to local contractors in terms of competition with other local and foreign contractors. Yet, a question arises whether the local contractors in particular are aware with the competitive challenges they are facing against the foreign contractors or even amongst the local contractors themselves. This is because there are limited studies conducted which seek to identify the current levels of awareness on competitiveness among local contractors within the Malaysian construction industry. Hence, this paper emerges with the objectives of (1) identifying the current level of awareness of local contractors on competitiveness and (2) investigating the most important attributes of awareness of local contractors in the Malaysian construction industry. Questionnaire surveys were conducted on local Malaysian contractors involving 61 organisations from 112 venturing into overseas market. Data were analysed via Rasch analysis consisting of fve method analysis which are the reliability and validity analysis, organisation misft analysis, unidimensionality analysis, item misft analysis and item measure order analysis. Findings from this paper reveal that most of the contractors have a moderate level of awareness on the competitiveness in the Malaysian construction industry. The fndings of this study have been concluded as the local contractors acknowledge their competitors' strength and weaknesses when bidding for new projects and also aim to improve their competitiveness in competing with other local contractors locally. Recognition of this paper on the awareness of the importance of competitiveness by various local contractors in the Malaysian construction industry is in line with the Construction Industry Transformation Plan (CITP) 2016–2020 in addressing the Internationalisation Thrust with the aim to increase competitiveness of the domestic market, especially with the presence of foreign players.